Detection and impacts of tiling artifacts in MODIS burned area classification. (5th February 2021) - Liu, Tianjia; Crowley, Morgan A
Abstract: Since 2000, observations from the Moderate Resolution Imaging Spectroradiometer (MODIS) instrument, aboard the Terra and Aqua satellites, have been used to monitor global burned area and its trends. The FireCCI and MCD64A1 products classify burned area using algorithms that detect change in surface reflectance and separately process each ∼10° × 10° MODIS tile. We find that artifacts arise in both products from this tiling procedure. In particular, we find severe tiling artifacts in FireCCI, version 5.1 (FireCCI51) in northwest India and Pakistan, where the classified burned area is disjointed at the latitudinal boundary of two tiles that largely separates the Indian states of Punjab and Haryana. In contrast, this tiling effect is less noticeable in MCD64A1, Collection 6 (C6). As a result, while the average 2003–2019 October-November burned area in Haryana is of similar magnitude across the two products, that for Punjab is 13, 381 km 2 for MCD64A1 and just 1, 486 km 2 for FireCCI. We find moderate tiling artifacts in Southeast Asia and Eastern Europe. Our results highlight that additional processing is needed to ensure the continuity of burned area classification in FireCCI and MCD64A1, as well as other products relying on tile-dependent algorithms.